2006
DOI: 10.1523/jneurosci.0309-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Composition of the Endocannabinoid System at Glutamatergic Synapses

Abstract: Endocannabinoids play central roles in retrograde signaling at a wide variety of synapses throughout the CNS. Although several molecular components of the endocannabinoid system have been identified recently, their precise location and contribution to retrograde synaptic signaling is essentially unknown. Here we show, by using two independent riboprobes, that principal cell populations of the hippocampus express high levels of diacylglycerol lipase ␣ (DGL-␣), the enzyme involved in generation of the endocannab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
452
4
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(509 citation statements)
references
References 53 publications
45
452
4
3
Order By: Relevance
“…CB 1 Rs are most densely expressed at cortical and hippocampal presynaptic γ-aminobutyric acid (GABA)ergic presynaptic boutons, especially cholecystokinin-positive (CCK+) and parvalbumin-negative GABAergic interneurons [64][65][66]. Glutamatergic axon terminals in cortical and subcortical neurons contain fewer presynaptic CB1 receptors than GABAergic terminals [65,[67][68][69][70][71].…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…CB 1 Rs are most densely expressed at cortical and hippocampal presynaptic γ-aminobutyric acid (GABA)ergic presynaptic boutons, especially cholecystokinin-positive (CCK+) and parvalbumin-negative GABAergic interneurons [64][65][66]. Glutamatergic axon terminals in cortical and subcortical neurons contain fewer presynaptic CB1 receptors than GABAergic terminals [65,[67][68][69][70][71].…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…At these stages, the CB 1 receptor is also present in the subpial area of the ganglionic eminences and the primordium of the hippocampus [15]. Later, CB 1 receptors are heterogeneously distributed through cortical layers and the hippocampus, in both excitatory glutamatergic projection neurons, as identified by vGlut1 expression, and cholecystokinin (CCK)-expressing GABAergic interneurons colabelled with vGlut3 [16][17][18]. CB 1 þ CCK þ interneurons derived from the ganglionic eminences follow tangential migratory routes from the ventral telencephalon and reach the developing cortex, hippocampus and amygdala [15,[19][20][21].…”
Section: The Endocannabinoid System In the Developing Brainmentioning
confidence: 99%
“…4). Type I mGluR, PLC-β and DGL-α are localized at the perisynapse (light red), a region of the dendritic spine that borders the postsynaptic density (purple) [63][64][65][66] . 2-AG crosses the synaptic cleft and activates presynaptic CB 1 cannabinoid receptors (CB 1 R), which suppress glutamate release.…”
Section: Flippasementioning
confidence: 99%
“…Immunogold electron-microscopy studies of hippocampal and cerebellar neurons have shown that this lipid hydrolase is primarily localized in a subdivision of the dendritic spine, called the perisynapse, which forms a thin border (100-200 nm thick) around the postsynaptic density 63,64 . Along with DAG lipase α, this same area also contains type I mGlurs 65 and phospholipase C-β 66 , and might, thus, be viewed as a stable perisynaptic site for the receptor-operated release of 2-AG.…”
Section: Neurosteroidmentioning
confidence: 99%
See 1 more Smart Citation